Public health impact of booster vaccination against COVID-19 in the UK during Delta variant dominance in autumn 2021. (31st December 2022) - Mendes, Diana; Chapman, Ruth; Gal, Peter; Atwell, Jessica; Nguyen, Jennifer L.; Hamson, Libby; Di Fusco, Manuela; Czudek, Carole; Yang, Jingyan
Abstract: Aim: To evaluate the public health impact of the UK COVID-19 booster vaccination program in autumn 2021, during a period of SARS-CoV-2 Delta variant predominance. Materials and methods: A compartmental Susceptible-Exposed-Infectious-Recovered model was used to compare age-stratified health outcomes for adult booster vaccination versus no booster vaccination in the UK over a time horizon of September–December 2021, when boosters were introduced in the UK and the SARS-CoV-2 Delta variant was predominant. Model input data were sourced from targeted literature reviews and publicly available data. Outcomes were predicted COVID-19 cases, hospitalizations, post-acute sequelae of COVID-19 (PASC) cases, deaths, and productivity losses averted, and predicted healthcare resources saved. Scenario analyses varied booster coverage, virus infectivity and severity, and time horizon parameters. Results: Booster vaccination was estimated to have averted approximately 547, 000 COVID-19 cases, 36, 000 hospitalizations, 147, 000 PASC cases, and 4, 200 deaths in the UK between September and December 2021. It saved over 316, 000 hospital bed-days and prevented the loss of approximately 16.5 million paid and unpaid patient work days. In a scenario of accelerated uptake, the booster rollout would have averted approximately 3, 400 additional deaths and 25, 500 additional hospitalizations versus the base case. A scenario analysis assuming four-fold greater virus infectivity and lower severity estimated that booster vaccination would have averted over 105, 000 deaths and over 41, 000 hospitalizations versus the base case. A scenario analysis assuming pediatric primary series vaccination prior to adult booster vaccination estimated that expanding vaccination to children aged ≥5 years would have averted approximately 51, 000 additional hospitalizations and 5, 400 additional deaths relative to adult booster vaccination only. Limitations: The model did not include the wider economic burden of COVID-19, hospital capacity constraints, booster implementation costs, or non-pharmaceutical interventions. Conclusions: Booster vaccination during Delta variant predominance reduced the health burden of SARS-CoV-2 in the UK, releasing substantial NHS capacity.